Dexmedetomidine Improves Locomotor Function and Alleviates Thermal Hyperalgesia Following Sciatic Nerve Crush Injury in Rats - Myung-Soo Jang; Jin Hee Han; Dong-Ok Kim; Gil Woo; Jae-Ik Kwon; Jun-Young Chung; Bong-Jae Lee; Jae-Woo Yi (International Neurourology Journal, 2020)
Purpose The effects of dexmedetomidine on locomotor function and thermal hyperalgesia in sciatic nerve crush injury (SNCI) were investigated using rats. Methods After exposing the right sciatic nerve, the sciatic nerve was crushed for 1 minute by a surgical clip. One day after nerve injury, dexmedetomidine (5, 25, and 50 µg/kg) was directly applied to the injured sciatic nerve once a day for 14 days. Walking track analysis was used to assess locomotor function and plantar test was conducted to assess thermal pain sensitivity. Immunohistochemistry was performed to determine the expression of c-Fos in the ventrolateral periaqueductal gray (vlPAG) and paraventricular nucleus (PVN). Western blot was used to evaluate the expression level of nerve growth factor (NGF) and myelin basic protein (MBP) in the sciatic nerve. Results SNCI resulted in deterioration of locomotor function and increased thermal pain sensitivity. The level of c-Fos expression in the PVN and vlPAG was increased and the level of NGF and MBP expression in the sciatic nerve was enhanced by SNCI. Dexmedetomidine treatment improved locomotor function and upregulated expression of NGF and MBP in the sciatic nerve of SNCI. Dexmedetomidine treatment alleviated thermal hyperalgesia and downregulated expression of c-Fos in the vlPAG and PVN after SNCI. Conclusions Dexmedetomidine may be used as a potential new treatment drug for recovery of locomotion and control of pain in peripheral nerve injury.